Review on Strategic Human Resource Management - Mohanty, Sasmita; Pradhan, Bibhuti B (International Journal of Psychosocial Rehabilitation, 2019)
The aim of this paper is to discuss the important relationship between the High Performance Working System (HPWS) as the main component of Strategic Human Resource Management (SHRM) and organizational performance as the basis for the determination of sustainable competitive advantage. It also explores the link between HR strategy and business strategy. Findings validated the association between SHRM-HPWS and the financial as well as non-financial (employee outcome) organizational performance based on literature review as demonstrated. HR strategy is also linked to business strategy as it contributes to maintaining high-quality customer satisfaction, performing high-quality, loving employees, and maintaining employee dedication and commitment to the organization for successful and sustainable competitive advantage. It thus strengthens employee growth, motivation and willingness to remain in the company longer. To conclude, to maintain the competitive advantage, organizational efficiency can be achieved through different sources. Also the conceptual framework illustrates how the study comes into conclusion.